Eccrine poroma: The prominent mimicker - Shihab, Nahla; Kristanti, Inge Ade; Sampurna, Adhimukti T.; Wibawa, Larisa Paramitha (UI Scholars Hub, 2018)
Background: Eccrine poroma (EP) is an adnexal benign tumor arising from the eccrine duct epithelium. The appearance of EP can mimic benign and malignant skin tumors, thus often making the diagnosis delayed or inaccurate. Case Illustration: We report two cases of EP, with clinical and dermoscopic features mimicking Bowen’s disease, verruca vulgaris, pyogenic granuloma, skin metastases of breast cancer, and amelanotic melanoma. Both patients were surgically excised and biopsied. Histopathology examination of both cases revealed eccrine poroma. Discussion: Both cases showed similarity with the theories, that EP is most found in middle age population and its predilection on extremities. The dermoscopy appearance of the first patient showed two major components, multiple red dots and lacunae mimicking glomerular vessels, and multiple whitish halos-likekeratosis. Red dots with whitish halos can be seen in dermoscopy of verruca vulgaris, while glomerular vessels and keratosis is usually found in Bowen’s disease. The dermoscopy examination of our second patient only showed some loop hemorrhagic and thrombosed vessels, which are quite inconclusive. Diagnoses were made with histopathology examination which revealed similar pattern of eccrine poroma in both cases. Conclusion: EP is a prominent mimicker, often misdiagnosed because it is uncommon in clinical practice, has variable clinical presentations and dermoscopic appearances. Hence, recognizing and diagnosing this disease becomes a challenge for dermatologist.